Giant tunable magnetoresistance of electrically gated graphene ribbon with lateral interface under magnetic field - Kadigrobov, A.M. (Физика низких температур, 2017)
Quantum dynamics and kinetics of electrically gated graphene ribbons with lateral n–p and n–p–n junctions under magnetic field are investigated. It is shown that the snake-like states [C. W. J. Beenakker, Rev. Mod. Phys. 80, 1337 (2008)] of quasiparticles skipping along the n–p interface do not manifest themselves in the main semi-classical part of the ribbon conductance. Giant oscillations of the conductance of a ribbon with an n–p–n junction are predicted and analytically calculated. Depending on the number of junctions inside the ribbon its magneto-resistance may be controllably changed by 50%–90% by an extremely small change of the magnetic field or the gate voltage.